BASIC LIFE SUPPORT- A STITCH IN TIME - Mohan, Muralee; Prasad, Rajendra; Sharma, S.M.; Shetty, Deepthi; Pandya, Kalpa (Journal of Health and Allied Sciences NU, 2014)
Basic Life Support is the identification of emergency medical conditions such as stroke, cardiac arrest, foreign body obstruction; cardiopulmonary resuscitation (CPR) and defibrillation. The main aim of CPR is to increase the blood supply to the brain and the heart. Any delay in providing CPR reduces the chances of survival for the victim. Thus timely CPR is also mandatory. Training in Basic life Support skills is a must for medical and paramedical professionals and students. Moreover, it is essential to train even the layman in these skills as bystanders are the first and the best rescuers if trained adequately. American Heart Association (AHA) guidelines are one of the most widely accepted ones in terms of measures for basic life support. These guidelines are updated every five years. The last update was in 2010. Through, this article an attempt has been made to throw light on the 2005 protocol and 2010 updates as recommended by AHA.
Keywords: cardiac arrest; cardiopulmonary resuscitation; rescue breaths; chest compressions